On Design of Contracts Between Traditional MNOs and Local 5G Micro Operators - Bidushi Barua; Marja Matinmikko-Blue; Matti Latva-aho (International Telecommunications Society (ITS), 2019)
Local 5G networks in specific geographical areas can satisfy local capacity, coverage needs, and offer context specific services to complement Mobile Network Operator's (MNOs') offerings. For enabling the emergence of these networks into the future mobile communication market, it is necessary to determine the contractual relationships possible for different deployments of these networks. We define the features of such contracts and the factors such as competition, level of differentiation in services offered, price structure, price transparency, and the role of regulation, that will influence these contracts, taking into account the characteristics of 5G and beyond networks. A mathematical model of a pricing mechanism is proposed to determine the optimal price the local network deserves to get from the MNO and the optimal price which the MNO demands from its customers that were served by the local network. Finally, the impact of competition in the retail market, fraction of MNO customers served by the local network, on these prices are analyzed and presented using simulations. The results indicate that lower the share of MNO customers served by the 5G local network, the stronger is the incentive of the corresponding local network to increase its optimal wholesale price. Moreover, the local 5G network gains from a greater competition between MNOs as it leads to the rise in demand without the local network having to reduce the prices they demand from the MNOs for their services.
Keywords: 330; Competition; contracts; micro operator networks; pricing mechanism; regulation